METODOLOGIA INSTRUIRII CENTRATE PE STUDENT ÎN CONTEXTUL CONDIŢIILOR DE OPTIMIZARE A APLICĂRII METODELOR REAL-ACTIVE ÎN FORMAREA INIŢIALĂ A CADRELOR DIDACTICE - USM ADMIN (Moldova State University, 2009)
The present article is a theoretical and practical study that elucidates the application of real-active methods in initial teachers forming. The authors have developed and implemented: the conditions and strategies of applying real-active methods in higher pedagogical education, student-centered methodology and matrix application methods covered in cognitive and meta-cognitive context. The study is valuable in research and theoretical aspects of combining organic and radiological, by addressing inter-, multi- and real-active trans-disciplinary methods of applying in training teachers. Time is thoroughly characteristic for methods, strategies, methodology applied in initial teachers forming.